(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2024)
The Ethiopic Bible manuscripts have a long history. Dillmann1 writes emphatically of the Ethiopic Bible that it was 'the foundation of all Abyssinian literature and the standard to which all other writers conformed their style of writing.'2 But the values of Ethiopic Bible manuscripts have not been studied well, using Philological and linguistic tools of study. Besides the main body of the text, the information that the marginalia hold is not well examined for historical and linguistic reconstructions. This is not to deny that Ge’ez manuscripts have been studied well by many scholars; however, thorough research on the values of the manuscripts or the Bible, in the same way, has not yet been done. Therefore, very little has been achieved from a diachronic viewpoint. Scholars used to claim that there were no manuscripts that came down to us from the Axumite period. That is why they conclude that the Axumite period is only the period of inscription.